2007
DOI: 10.1007/s00125-007-0800-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macrophage migration inhibitory factor (MIF) gene variants and MIF serum concentrations on the risk of type 2 diabetes: results from the MONICA/KORA Augsburg Case–Cohort Study, 1984–2002

Abstract: Aims/hypothesis Macrophage migration inhibitory factor (MIF) is a central mediator of innate immunity. Our aim was to investigate the triangular association between MIF genotypes, circulating MIF concentrations and incident type 2 diabetes, and to use a Mendelian randomisation approach to assess the causal role of MIF. Methods Using a case-cohort design within the population-based MONICA/KORA Augsburg Study, based on 502 individuals with incident type 2 diabetes (293 men, 209 women) and 1,632 non-cases (859 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 49 publications
2
79
0
Order By: Relevance
“…On this source population, we applied a case-cohort study consisting of a random sample (called subcohort; nZ1885) of the source population stratified by sex and survey, and all incident T2DM cases (nZ555) in the source population diagnosed up to December 31, 2002 as it was described more detailed previously (31,(35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%
“…On this source population, we applied a case-cohort study consisting of a random sample (called subcohort; nZ1885) of the source population stratified by sex and survey, and all incident T2DM cases (nZ555) in the source population diagnosed up to December 31, 2002 as it was described more detailed previously (31,(35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%
“…Prospective studies have demonstrated that elevated circulating concentrations of several acute-phase proteins, cytokines, chemokines and soluble adhesion molecules precede the development of type 2 diabetes by many years [8][9][10][11][12][13][14]. Among these immune mediators, C-reactive protein (CRP) and IL-6 have been investigated for potential associations with incident type 2 diabetes in most prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…While most of these studies were performed in the setting of stress, several reports have also documented an association between MIF, obesity, and insulin resistance (IR) in a physiological environment. MIF secretion and serum concentration are increased in obese individuals or in patients with type 2 diabetes (Church et al 2005, Skurk et al 2005, Herder et al 2008, and a polymorphism in the MIF gene promoter has been linked to obesity (Sakaue et al 2006). In addition, several reports have described that an elevated level of MIF is associated with decreased b-cell function and IR (Benigni et al 2000, Church et al 2005, Sakaue et al 2006).…”
Section: Introductionmentioning
confidence: 99%